Preparation method of high-performance composite hydrogel and application of high-performance composite hydrogel in gesture recognition
By introducing crosslinking agent and lithium chloride into the hydrogel, it improves its strength and conductivity, and solves the problem of taking into account both high tensile magnification and stability, and realizes the preparation of high-performance hydrogels and the successful application in gesture recognition.
Patent Information
- Application Number
- CN202411725527.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
AI Technical Summary
The existing hydrogels have low strength while having high tensile magnification, and are difficult to take into account both stability and conductivity in cold environments or low humidity, resulting in susceptible to environmental factors during signal acquisition, large signal fluctuations, making it difficult to accurately extract information.
The crosslinking agent is prepared by the strategy of mutual dissolution of polar molecules, and mixed with acrylamide monomer, lithium chloride, surfactant and initiator to heat polymerization to produce a multifunctional hydrogel, which has high tensile, high toughness, high conductivity and anti-freeze moisturizing properties.
The high strength (break stress: 0.3MPa), high elongation (30-50 times) and high conductivity (6S/m) of the hydrogel are achieved, which meets the mechanical performance requirements in different limb signal measurement scenarios. Through its application in gesture recognition, the accurate recognition and information extraction of human sign language gestures are achieved, and the recognition accuracy can reach 100%.
Smart Images

Figure CN119552303A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer materials and flexible electronic technology, and in particular to a preparation method of a high-performance composite hydrogel and an application of the same in gesture recognition. Background Art
[0002] Hydrogels have many advantages, such as excellent stretchability, biocompatibility, and wearability. They can better fit on human skin or the surface of objects. In addition, they can withstand a certain degree of bending and stretching and adapt to complex movements and deformations. Therefore, hydrogels have broad application prospects in the field of wearable electronic devices.
[0003] In the application scenarios of wearable electronic devices, hydrogels are used for bio-signal collection, such as human joint movements and smaller amplitude breathing, vocal cord vibration, pulse, etc. In general, hydrogels require high stretching ratios to cope with scenarios with large local deformations. In the prior art, hydrogels obtained by hydrophobic polymerization of micellar solutions usually have a large stretching ratio, which meets the high stretching ratio requirements of wearable electronic devices. However, the hydrogel synthesized by this method has a low strength, usually only tens of kilopascals, which makes it very limited in working scenarios. Under the premise of ensuring the high stretching ratio of the hydrogel, it is of great significance to improve the strength of the hydrogel.
[0004] In addition, hydrogels usually need to have high stability to meet working requirements. By replacing water with organic solvents such as glycerol, the hydrogel has better antifreeze and anti-drying properties, ensuring that the hydrogel can work stably in cold environments or low humidity. However, the conductivity of the hydrogel is poor after solvent replacement. Therefore, it is difficult to take into account the stability and conductivity of the hydrogel. In addition, during the signal acquisition process of wearable electronic devices using hydrogels as sensors, the hydrogel itself is easily affected by environmental factors, resulting in signal fluctuations and lack of high repeatability. Therefore, accurately extracting information from the signal is also a major challenge. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a high-performance composite hydrogel and its application in gesture recognition. A cross-linking agent is prepared by a strategy of mutual solubility of polar molecules, and then mixed with acrylamide monomer, lithium chloride, a surfactant and an initiator into a solution, and thermally polymerized to obtain a multifunctional hydrogel with high stretchability, high toughness, high conductivity and antifreeze and moisture retention, meeting the requirements of practical work on the mechanical and electrical properties and environmental stability of the hydrogel.
[0006] To achieve the above object, the present invention provides a method for preparing a high-performance composite hydrogel, comprising the following steps:
[0007] S1, according to a certain ratio, divinylbenzene is added to octavinyl-POSS, and stirred to obtain a layered solution, and the uniformly dispersed upper layer solution is taken as a cross-linking agent;
[0008] S2. Dissolve acrylamide monomer and lithium chloride in deionized water in a certain proportion, then add initiator and surfactant, stir evenly, then add the crosslinker obtained in S1, stir well for two hours and then let stand for four hours, take out the lower layer of solution and obtain hydrogel through thermal polymerization reaction.
[0009] Preferably, in S1, the mass ratio of divinylbenzene to octavinyl-POSS is 50:2-3.
[0010] Preferably, in S1, the stirring treatment is carried out at a temperature of 22 to 26°C, for a time of 25 to 30 minutes, and at a rotation speed of 200 to 300 r / min.
[0011] Preferably, in S2, the mass ratio of the acrylamide monomer, the surfactant, the initiator, the cross-linking agent, the deionized water and the lithium chloride is 100:2.5-3.5:1-1.25:7.5-10:350-500:18-24.
[0012] Preferably, in S2, the initiator is one of potassium persulfate or ammonium persulfate, and the surfactant is sodium dodecyl sulfate.
[0013] Preferably, in S2, the stirring temperature is 22-26° C., and the stirring speed is 200-300 r / min.
[0014] Preferably, in S2, the temperature of the thermal polymerization reaction is 55-60° C., and the time is 5-6 hours.
[0015] To achieve the above object, the present invention provides an application of a high-performance composite hydrogel in gesture recognition.
[0016] Preferably, the hydrogel is attached to the finger joints as a flexible strain sensor, and the bending signals of each finger joint are measured as the bending signals of different sign language gestures. A sign language gesture signal data set is constructed, and the data set is used to train an artificial neural network, through which the artificial neural network successfully recognizes the signals of human sign language gestures and extracts information.
[0017] Therefore, the present invention adopts the above-mentioned method for preparing a high-performance composite hydrogel and its application in gesture recognition, and the beneficial effects are as follows:
[0018] (1) The present invention adopts a mixed crosslinking agent of octaethylene-POSS (POSS) and divinylbenzene (DVB solution). The POSS molecule has eight vinyl double bonds and has a super strong ability to crosslink molecules. However, the POSS molecule is poorly soluble in water and slightly soluble in most organic solvents, while the POSS molecule has a good mutual solubility with the DVB solution. The POSS molecules are dispersed in the DVB solution to prepare a new mixed crosslinking agent, which significantly improves the toughness of the hydrogel. In addition, POSS is successfully introduced through a mixed crosslinking agent strategy, which is universal and suitable for introducing other solutes or crosslinking agents with poor solubility.
[0019] (2) The present invention uses lithium chloride, which, on the one hand, improves the ionic conductivity of the hydrogel; on the other hand, since lithium atoms have the property of easily combining with water molecules, the hydrogel has antifreeze and moisturizing properties. Under normal circumstances, the hydrogel will gradually lose water and harden at room temperature, while the hydrogel with the addition of lithium chloride will lose less water in the same environment. Even after drying, it has the ability to gradually absorb water from the environment and maintain a certain water content, so that the hydrogel maintains its own softness, and this ability is positively correlated with the content of lithium chloride.
[0020] (3) The hydrogel prepared by the present invention has high strength (fracture stress: 0.3MPa), high elongation (30-50 times), and high conductivity (6S / m), which meets the mechanical performance requirements such as local large deformation and working intensity in different limb signal measurement scenarios. The hydrogel was used as a flexible strain sensor to successfully measure the signals of different gestures, and a sign language gesture signal data set was constructed. The data set was used to train the artificial neural network, which solved the problem that the test signal of the hydrogel as a flexible strain sensor is prone to fluctuation, and achieved accurate information extraction from the signal, and realized the recognition of human sign language gestures, and its recognition accuracy can reach 100%.
[0021] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a morphology diagram of Example 1 of a method for preparing a high-performance composite hydrogel of the present invention;
[0023] Figure 2 This is a morphology diagram of Example 2 of a method for preparing a high-performance composite hydrogel of the present invention;
[0024] Figure 3 It is a tensile stress-strain curve diagram of Examples 1, 2 and 6 of a method for preparing a high-performance composite hydrogel of the present invention;
[0025] Figure 4It is the tensile stress-strain curve of Examples 2 to 5 of the method for preparing a high-performance composite hydrogel of the present invention;
[0026] Figure 5 This is an impedance diagram of Example 2 of a method for preparing a high-performance composite hydrogel of the present invention;
[0027] Figure 6 This is an impedance diagram of Example 6 of a method for preparing a high-performance composite hydrogel of the present invention. DETAILED DESCRIPTION
[0028] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0029] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0030] Embodiment 1
[0031] 2g acrylamide monomer (AM), 0.02g potassium persulfate and 0.06g sodium dodecyl sulfate were added to a beaker, and then 8ml deionized water was added, and stirred at room temperature and 200r / min for 30min. When all the solutes were completely dissolved, that is, sodium dodecyl sulfate formed uniform micelles in the solution, and a clear and transparent solution was obtained, 200μl DVB solution was added to the solution, and then the beaker mouth was covered with a glass sheet and continued to be stirred for 2h, and allowed to stand for 4h to obtain a lower layer of a transparent aqueous solution with a layer of yellow oil floating on the surface. At this time, the lower layer of transparent aqueous solution was taken and poured into a mold, and reacted at 60°C for 6h to obtain P(AM-DVB) hydrogel.
[0032] like Figure 1 As shown, the pore size of P(AM-DVB) hydrogel is 20-30 μm.
[0033] Embodiment 2
[0034] S1. Add 0.06g POSS molecule into a 5ml beaker, then add 1ml DVB solution with a purity of 55%, and stir at 200r / min for 30min at room temperature. At this time, the solution is divided into two layers, the upper layer is a white translucent solution, and the lower layer is an incompletely dissolved POSS powder. Take the upper solution as a new cross-linking agent.
[0035] S2, 2g acrylamide monomer, 0.02g potassium persulfate and 0.06g sodium dodecyl sulfate were added to a beaker, and then 8ml deionized water was added, and stirred at 200r / min at room temperature for 30min, all solutes were completely dissolved, that is, sodium dodecyl sulfate formed uniform micelles in the solution, and a clear and transparent solution was obtained. At this time, 200μl of the cross-linking agent prepared in step S1 was added to the solution, and then the beaker mouth was covered with a glass sheet and continued to be stirred for 2h, and allowed to stand for 4h to obtain a lower layer of a transparent aqueous solution and a layer of oily substance mixed with POSS powder floating on the surface. The lower layer solution was taken out and poured into a mold, and reacted at 60°C for 6h to obtain P(AM-POSS-DVB) hydrogel.
[0036] like Figure 2 As shown, the pore size of the P(AM-POSS-DVB) hydrogel is 5 to 20 μm, which indicates that the P(AM-POSS-DVB) hydrogel has a higher cross-linking density and cross-linking uniformity compared to the P(AM-DVB) hydrogel of Example 1.
[0037] Embodiment 3
[0038] The difference from the second embodiment is that in step S2, the amount of deionized water added is changed from 8 ml to 7 ml.
[0039] Embodiment 4
[0040] The difference from the second embodiment is that in step S2, the amount of deionized water added is changed from 8 ml to 9 ml.
[0041] Embodiment 5
[0042] The difference from the second embodiment is that in step S2, the amount of deionized water added is changed from 8 ml to 10 ml.
[0043] Embodiment 6
[0044] S1. Add 0.06g POSS molecule into a 5ml beaker, then add 1ml DVB solution with a purity of 55%, and stir at 200r / min for 30min at room temperature. At this time, the solution is divided into two layers, the upper layer is a white translucent solution, and the lower layer is an incompletely dissolved POSS powder. Take the upper solution as a new cross-linking agent.
[0045] S2, 2g acrylamide monomer, 0.02g potassium persulfate, 0.06g sodium dodecyl sulfate and 0.48g lithium chloride are added to a beaker, and then 8ml deionized water is added, and stirred at 200r / min at room temperature for 30min, until all solutes are completely dissolved, that is, sodium dodecyl sulfate forms uniform micelles in the solution to obtain a clear and transparent solution, at this time, 200μl of the cross-linking agent prepared in step S1 is added to the solution, and then the beaker mouth is covered with a glass sheet and continued to stir for 2h, and allowed to stand for 4h to obtain a lower layer of a transparent aqueous solution and a layer of oily substance mixed with POSS powder floating on the surface, the lower layer solution is taken out and poured into a mold, and reacted at 60°C for 6h to obtain P(AM-POSS-DVB) / LiCl hydrogel.
[0046] Experimental Testing
[0047] The hydrogels prepared in Examples 1 to 6 were subjected to tensile tests respectively.
[0048] like Figure 3 As shown, the stress-strain curves of the tensile test of the hydrogels prepared in Example 1, Example 2 and Example 6 indicate that the addition of POSS molecules and lithium chloride enhances the strength of the hydrogels.
[0049] like Figure 4 As shown, the stress-strain curves of the tensile test of the hydrogels prepared in Example 2, Example 3, Example 4 and Example 5 indicate that the toughness and stretching ratio of the hydrogels are adjustable within a range.
[0050] The hydrogels prepared in Example 2 and Example 6 were used to perform impedance tests respectively.
[0051] like Figure 5 and Figure 6 As shown, compared with P(AM-POSS-DVB) hydrogel, the impedance of P(AM-POSS-DVB) / LiCl hydrogel is reduced by one order of magnitude, indicating that lithium chloride improves the ionic conductivity of the hydrogel.
[0052] The hydrogel prepared in Example 6 was used to conduct low temperature and real environment simulation tests.
[0053] The P(AM-POSS-DVB) / LiCl hydrogel remains soft at -20°C and does not completely lose water and become hard after long-term exposure to air, and can still maintain a high water content; after being completely dried, it has the ability to gradually absorb water from the environment.
[0054] In summary, the high-performance composite hydrogel has an antifreeze ability of -20°C, a breaking stress of 0.3MPa, an elongation of 30 to 50 times, and a conductivity of 6S / m.
[0055] Hydrogels are used as strain sensors for human sign language gesture signal recognition. The hydrogels are attached to the finger joints, and different voltage signal outputs correspond to different degrees of finger bending. The signals are collected through the ADC module, and data sets corresponding to different gestures are constructed. Labels representing different gestures are assigned for machine learning training. The constructed artificial neural network successfully recognizes the gestures of numbers 0 to 9 and letters A to Z. After multiple iterations of training, its accuracy rate reaches 100%.
[0056] Therefore, the present invention adopts the above-mentioned preparation method of a high-performance composite hydrogel and its application in gesture recognition, prepares a cross-linking agent through the strategy of mutual solubility of polar molecules, and then mixes it with acrylamide monomer, lithium chloride, surfactant and initiator to form a solution, and thermally polymerizes it to obtain a multifunctional hydrogel with high stretchability, high toughness, high conductivity and antifreeze and moisture retention, which meets the requirements of practical work on the mechanical and electrical properties and environmental stability of hydrogels.
[0057] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a high-performance composite hydrogel, characterized in that: The following steps are involved: S1, according to a certain ratio, divinylbenzene is added to octavinyl-POSS, and stirred to obtain a layered solution, and the uniformly dispersed upper layer solution is taken as a cross-linking agent; S2. Dissolve acrylamide monomer and lithium chloride in deionized water in a certain proportion, then add initiator and surfactant, stir evenly, then add the crosslinker obtained in S1, stir well for two hours and then let stand for four hours, take out the lower layer of solution and obtain hydrogel through thermal polymerization reaction.
2. The method for preparing a high-performance composite hydrogel according to claim 1, characterized in that: In S1, the mass ratio of divinylbenzene to octavinyl-POSS is 50:2-3.
3. The method for preparing a high-performance composite hydrogel according to claim 1, characterized in that: In S1, the stirring treatment is carried out at a temperature of 22 to 26°C, for a time of 25 to 30 minutes, and at a rotation speed of 200 to 300 r / min.
4. The method for preparing a high-performance composite hydrogel according to claim 1, characterized in that: In S2, the mass ratio of the acrylamide monomer, the surfactant, the initiator, the cross-linking agent, the deionized water and the lithium chloride is 100:2.5-3.5:1-1.25:7.5-10:350-500:18-24.
5. The method for preparing a high-performance composite hydrogel according to claim 1, characterized in that: In S2, the initiator is one of potassium persulfate or ammonium persulfate, and the surfactant is sodium dodecyl sulfate.
6. The method for preparing a high-performance composite hydrogel according to claim 1, characterized in that: In S2, the stirring temperature is 22-26°C, and the stirring speed is 200-300 r / min.
7. The method for preparing a high-performance composite hydrogel according to claim 1, characterized in that: In S2, the temperature of the thermal polymerization reaction is 55-60°C and the time is 5-6 hours.
8. Use of a hydrogel prepared by the method for preparing a high-performance composite hydrogel according to any one of claims 1 to 7 in gesture recognition.
9. The use of a high-performance composite hydrogel in gesture recognition according to claim 8, characterized in that: The hydrogel is attached to the finger joints as a flexible strain sensor, and the bending signals of each finger joint are measured as the bending signals of different sign language gestures. A sign language gesture signal data set is constructed, and the data set is used to train an artificial neural network. The artificial neural network can successfully identify the signals of human sign language gestures and extract information.